Development of Digital Competence in Secondary Education Teachers' Training - María Napal Fraile; Alicia Peñalva-Vélez; Ana María Mendióroz Lacambra (MDPI AG, 2018)
Digital competence is one of the eight key competences for life-long learning developed by the European Commission, and is a requisite for personal fulfilment and development, active citizenship, social inclusion, and employment in a knowledge society. To accompany young learners in the development of competence, and to guarantee optimal implementation of information and communication technologies (ICTs), it is necessary that teachers are, in turn, literate. We had 43 secondary school teachers in initial training to assess their own level of competence in 21 sub-competences in five areas identified by the DIGCOMP project, using the rubrics provided in the Common Digital Competence Framework for Teachers (Spanish Ministry of Education). Overall, pre-service teachers’ conceptions about their level of digital competence was low (Initial). Students scored highest in information, which refers mostly to the operations they performed while being students. Secondly, in safety and communication, excluding protection of digital data and preservation of digital identity. Lowest values were achieved in content creation and problem solving, the dimensions most closely related with the inclusion of ICTs to transform teaching-learning processes. The knowledge or skills they exhibit are largely self-taught and, so, we perceive an urgent need to purposefully incorporate relational and didactic aspects of ICT integration.